Connection between Dupuytern’s contracture and plantar aponeurosis - Almohideb, Malik; Alziady, Dhaifallah; Alotaibi, Hazem; Alshehri, Fareed; Alsaif, Malak; Alkhunayfir, Hamad; Aljohani, Abdulaziz; Alrawaf, Talal; Shata, Abdulrahman; Alghamdi, Mohammed (International Journal Of Community Medicine And Public Health, 2018)
Dupuytren’s disease of the foot is not an uncommon disease that affects the plantar aponeurosis. It is a different clinical entity from Dupuytren’s contracture of hands. It presents clinically with slowly growing painless hard nodules on the medial aspects on the feet. Though the pathophysiological mechanisms remain elusive, hyperproliferation of fibroblasts and excessive synthesis of collagen fibers type III are proposed to be the main pathogenetic processes resulting in nodule development and growing. The most widely accepted theory for disease development is the combination of genetic predisposition and environmental risk factors such as smoking chronic alcohol consumption, diabetes mellitus, and other forms of superficial or dee fibromatosis. This article will discuss the dupuytren’s disease of the foot as regards the epidemiology, the pathophysiology, the clinical presentation, diagnosis, and lines of treatment. It will provide a special focus on the mechanisms of affection of plantar aponeurosis.